Pertoldite, trigonal GeO2, the germanium analog of α-quartz: a new mineral from Radvanice, Czech Republic - Zacek,V.; Skoda,R.; Laufek,F.; Sejkora,J.; Haifler,J. (Journal of Geosciences, 2022)
The new mineral pertoldite was found in a burning waste dump of abandoned Katerina colliery at Radvanice near Trutnov, Hradec Kralove Department, Czech Republic. The dump fire started spontaneously before 1980 and no anthropogenic material was deposited there. The determination of pertoldite as a natural analog of synthetic trigonal α-GeO2 is based on its chemical composition, X-ray powder diffraction data, and Raman spectroscopy. Pertoldite occurs as white to brownish aggregates resembling cotton tufts, up to 1 mm in size, composed of acicular crystals up to ˜1 μm thick and up to 1 mm in length. Individual crystals are distorted, resembling textile fibers. Pertoldite was formed by direct crystallization from hot (400-500 °C) gasses containing Cl and F as transporting agents at a depth of 40-60 cm under the surface of a burning coal mine dump. It nucleated as a thin, delicate crust on a chip of siltstone together with multi-component aggregates of galena, stibnite, bismuthian antimony, greenockite, and bismuth. The ideal formula of pertoldite, GeO2, requires 100 wt. % GeO2. Germanium is partially substituted by silica (2.33-5.67 wt. % SiO2), the extent of Ge1Si-1 substitution is limited to 0.03-0.09 apfu Si, and the empirical formula ranges between (Ge0.91-0.97Si0.03-0.09)Σ1.00O2. Pertoldite is trigonal, P3121 or P3221, a = 4.980(5) Å, c = 5.644(4) Å, with V = 121.2(2) Å3 and Z = 3. The strongest reflections of the powder X-ray diffraction pattern [d (Å)/I (hkl)] are: 4.315/44(100), 3.425/100(101,011), 2.490/31(110), 2.360/41(012,102), 1.867/31(112), 1.4179/31(023,203), 1.4124/37 (122,212). The crystal structure of pertoldite is based on corner-sharing [GeO4] tetrahedra forming a three-dimensional network similar to that of α-quartz. Pertoldite is named after Zdenek Pertold (1933-2020), professor of economic geology at the Faculty of Sciences, Charles University in Prague. The mineral and its name have been approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (number 2021-074) and the holotype specimen is deposited in the collections in the Department of Mineralogy and Petrology, National Museum in Prague, under the catalogue number P1P 31/2021.
Keywords: pertoldite; new mineral; germanium oxide; GeO2; pyrometamorphism; Radvanice